Synthesis, Characterization of New Tris Hydrazones based on Cyanuric Acid and Studies the Biological Activity as Antibacterial and Antifunga - Thaer Saleh Ghali (Institute of Medico-legal Publications Pvt Ltd, 2020)
In this study synthesis of new Tris Hydrazones derived from Cyanuric acid , these compounds synthesized by reaction of Cyanuric acid with Chloro ethyl acetate to product [I], then converted it to acid Hydrazide [II] by reacted with Hydrazine hydrate(80%) in absolute ethanol as a solvent. Compound [II] refluxed with different aromatic aldehyde in present of Glacial acetic acid (GAA) as a catalyst to formation new Tris Hydrazones [III]a-f. All new compounds were synthesized characterization by FT-IR and 1H-13CNMR spectroscopy. The biological activity of new Tris Hydrazones studies against to positive and negative Gram bacteria also test it against to Candida albicans as a sample of Fungi.